Arabic as a language of Islam Nusantara: The need for an Arabic Literature of Indonesia - Nico J.G. Kaptein (Center for Research and Development of Religious Literature and Heritage, 2017)
The term Islam Nusantara has been in circulation for a long time, but recently its use has gained a new significance after the 2015 Nahdlatul Ulama Congress in Jombang. Understanding of the term Islam Nusantara differs, but a common feature in all interpretations is the opinion that it is a blend of universal Islamic notions and specific regional cultural elementswith specific Indonesian characteristics, like tolerance, peacefulness and moderation.In the history of Islam in Indonesia different appreciations of Arabic as a language of Islam Nusantara exist. In this paper I want to go into the role of Arabic in Islam in Indonesia and I will argue that for a proper assessment of position of Arabic within the concept of Islam Nusantara an Arabic Literature of Indonesia should be produced.